God's work [compact disc] - Rimes, LeAnn (EverLe Records, 2022)
LeAnn Rimes has teamed up with some of music's biggest names on her new release that includes 12 tracks. Features Mickey Guyton, Ziggy Marley, Ledisi, Aloe Blacc and more!